If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying z = 2z + -70 Reorder the terms: z = -70 + 2z Solving z = -70 + 2z Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-2z' to each side of the equation. z + -2z = -70 + 2z + -2z Combine like terms: z + -2z = -1z -1z = -70 + 2z + -2z Combine like terms: 2z + -2z = 0 -1z = -70 + 0 -1z = -70 Divide each side by '-1'. z = 70 Simplifying z = 70
| (4x)(-3xy^2)= | | (4x+9)-(x+9)=33 | | -(12-x)=4 | | 3x+2(6x-4)=52 | | 3x+20=8x-4 | | x^2=22+3x | | -5c-12/4=2 | | 4x+5(-5x+9)=171 | | (3x-5)+(3x+5)=180 | | 9(3x+10)-20x=2x+115 | | -6j+7=8j-16j-13 | | m/16-3=(-2) | | 4a/3=10 | | -8(p+2)+p=4(p+3)+5 | | 5x+7=50 | | -x-14=1 | | 3y+8y-19=17+5y | | 10/60=x/100 | | 12-2(4x-5)=-2 | | 35=6v-5+4v | | 6(2x-1)+2(x+11)=2 | | X/x^4/24 | | (5x/2)-9=(2x-7/6) | | 0=3(2x+4) | | y=-3.5x-4.5 | | 6u-4u=10 | | 198=5x+3(-7x+2) | | (m=5)/5=3 | | 3x+25+-37=126 | | 44=2v | | -8x+5(2x-1)=4x+7 | | -4p+2+20p=15p+18 |